You've got a friend in me: how international governmental organizations influence organizations' participation in elections as ethnic parties in Eastern Europe. Issue 5 (4th July 2022) - Brandt, Caroline M.; Asal, Victor
ABSTRACT: Which ethnopolitical organizations run for office? An extensive literature studies when ethnic parties emerge. We explore an understudied dimension that distinguishes various ethnopolitical organizations: the support of international governmental organizations (IGOs). IGOs can encourage ethnopolitical organizations to participate in elections by lowering an organization's campaign costs or the price of internal restructuring. IGOs can also increase the expected benefits of running for office. Ties with an IGO communicate to voters that an organization will effectively represent the ethnic group domestically and internationally. We explore the case of Bosnia and Herzegovina, where the international community's hand is highly visible, to illustrate the mechanisms that link IGO support and organizations' participation in elections. We then use a large-N cross-national analysis, relying on original data of hundreds of ethnopolitical organizations from 1991–2006 throughout Eastern Europe, to assess the theory's generalizability. We use a recursive bivariate probit model to incorporate an estimate of which organizations IGOs are most likely to support into our analysis. Our results show that IGO support strongly correlates with an ethnopolitical organization running for office. This research contributes to our understanding of how ethnopolitical organizations with differing ideologies, competitive dynamics, and international ties come to represent an ethnic minority.